Analisis Implementasi Etika Bisnis Islam pada Usaha Jual Beli Mobil Bekas di PT Berlian Abadua Satu - Ahadin Sadri (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
The purpose of this study is to examine the extent to which Islamic business ethics variable affect Profitability, Customer satisfaction, Employee involvement, Business continuity, and Community involvement that has been implemented at PT Berlian Abadua One, Jakarta. This research approach is quantitative with survey method The study population is all of the stakeholder elements of the company, i.e owners of companies, consumers, employees, suppliers, government, and society. The sample was 100 respondents, and the sampling technique was incidental sampling. Data analysis technique is causal analysis by using Partial Least Squares (PLS)-Structural Equation Modeling (SEM), with the help of SmartPLS 3.0 software. The results show that Islamic business ethics influences the five dependent variables. Toward Profitability, the influence of Islamic business ethics is positive and significant; while for Customer satisfaction, Employee engagement, Business continuity, and Community involvement, the influence of Islamic business ethics are positive, but not significant. This study proves that Islamic business ethics is an independent variable that has predictive power, because the value of Q squares for five research models is greater than 0 (zero).